2021
DOI: 10.1039/d1cp00009h
|View full text |Cite
|
Sign up to set email alerts
|

Tracing absorption and emission characteristics of halogen-bonded ion pairs involving halogenated imidazolium species

Abstract: We investigate how the absorption and fluorescence of halogenated imidazolium compounds in acetonitrile solution is influenced by the presence of counterions and the ability to act as halogen-bond donors. Experimental...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…In fact, previously it has been shown that electronic spectroscopy can be useful in the study of halogen bond in molecular complexes. 32 It is known that a very efficient BF 2 -/BF-carrying fluorophores (similar to classical BODIPYs) hold a privileged spot due to high fluorescence quantum yields (FQYs) deriving from a rigid core in their structure. Similar rigidity, crucial for enhancing the radiative dissipation of excitation energy, is the characteristics of several close-relative families of dyes: boranils, 33,34 ketonates, 35,36 or ketoiminates.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, previously it has been shown that electronic spectroscopy can be useful in the study of halogen bond in molecular complexes. 32 It is known that a very efficient BF 2 -/BF-carrying fluorophores (similar to classical BODIPYs) hold a privileged spot due to high fluorescence quantum yields (FQYs) deriving from a rigid core in their structure. Similar rigidity, crucial for enhancing the radiative dissipation of excitation energy, is the characteristics of several close-relative families of dyes: boranils, 33,34 ketonates, 35,36 or ketoiminates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The present study contributes to these efforts and aims at studying the changes in electronic absorption and emission spectra upon interactions of an emissive pyridine-functionalized dye with perfluorohaloarenes (C 6 F 6 , C 6 F 5 Cl, C 6 F 5 Br, and C 6 F 5 I) in the two-component-only liquid phase. In fact, previously it has been shown that electronic spectroscopy can be useful in the study of halogen bond in molecular complexes …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, excitation of 6I into the S 1 ${\leftarrow }$ S 0 absorption band leads to homolytic cleavage of the iodine atom at C 6 with high quantum yield [60–63] . The resulting radicals in solution are stabilized by hydrogen abstraction from the solvent, while the iodine atoms combine to molecular iodine.…”
Section: Resultsmentioning
confidence: 99%